IХ All-Ukrainian Scientific Conference “Theoretical and Applied Aspects of Biography Studies: to the 170th anniversary of the birth of Mykola Fedorovych Sumtsov” - Aksyonova, Natalia; Vovk, Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
May 10, 2024 at Kharkiv National University named after V. N. The IX All-Ukrainian Scientific Conference "Theoretical and Applied Aspects of Biography: To the 170th Anniversary of the Birth of Mykola Fedorovych Sumtsov" was held in Karazin. The event was dedicated to the memory of an outstanding historian, ethnographer, museum worker, graduate and professor of Kharkiv University, who made an invaluable contribution to the study of the tangible and intangible cultural heritage of Slobozhanshchyna.